ANALISIS MENEJEMEN MARKETING DAN PELAYANAN PADA PT KAMILAH WISATA MUSLIM - Romzatul Widad; Risdatul Firoh (ITB AAS Indonesia Surakarta, 2024)
The development of the Hajj and Umrah travel business has given rise to selective competition. Choosing quality travel is important because many companies do not have legal operating permits. Good management in strategy, service and operations is very crucial to ensure the comfort and safety of the congregation, especially when in Saudi Arabia. PT. Kamilah Wisata Muslim is a company that operates in the field of Hajj and Umrah Services or known as PPIH (Hajj Travel Organizer). This research aims to analyze marketing and service management at PT Kamilah Wisata Islami, a company that organizes Hajj and Umrah pilgrimages. PT Kamilah Wisata Islami has official permission from the Department of Religion and is committed to guiding the congregation to carry out worship according to the Sunnah of the Prophet. This research uses a data presence and focuses on management, marketing and service concepts implemented by the company. This research uses a comparative type of qualitative research using primary and secondary data, namely interviews and observations. The results of the analysis show that the success of PT Kamilah Haji and Umroh in combining effective marketing management and quality service can be seen from the high level of satisfaction and trust of successful congregations. This travel does not escape good achievement management, especially marketing and service management. Keywords: Management, Marketing, Service